Polymer electrolytes for energy storage devices - Raghavan, Prasanth; Jabeen Fatima M. J. (Boca Raton : CRC Press, 2021)
Polymer Electrolytes for Energy Storage Devices, Volume I,offers a detailed explanation of recent progress and challenges in polymer electrolyte research for energy storage devices. The influence of these electrolyte properties on the performance of different energy storage devices is discussed in detail. Features: Discusses a variety of energy storage systems and their workings and a detailed history of LIBs Covers a wide range of polymer-based electrolytes including PVdF, PVdF-co-HFP, PAN, blend polymeric systems, composite polymeric systems, and polymer ionic liquid gel electrolytes Provides a comprehensive review of biopolymer electrolytes for energy storage applications Suitable for readers with experience in batteries as well as newcomers to the field This book will be invaluable to researchers and engineers working on the development of next-generation energy storage devices, including materials, chemical, electrical, and mechanical engineers, as well as those involved in related disciplines.
OCLC-licensed vendor bibliographic record.
Keywords: Storage batteries -- Materials; Solid state batteries -- Materials; Polyelectrolytes; SCIENCE / Chemistry / Industrial & Technical